Aristotle's notion of friendship as applied to the Filipino's concept of friendship an ethical perspective - Lat, Marlon Reyes (2013)
Ethics is significant in fulfilling the good of human life - happiness. Among the existing ethical theories, the virtue theory of Aristotle is the main framework used in trying to achieve such goal. Among the Aristotelian virtues, friendship is destructively helpful in human being's quest for happiness. A friend is man's evidence that makes him a social being. However, choosing the kind of friends that he/she wants to be valued the most is a significant factor to consider in this quest. Aristiotle discusses the types of friendship-based on benefit, pleasure and goodness - as the best venue for determining who ought to be one's real friends. This article presents a comparative analysis of Aristotle's notion of friendship and Filipono's concept of friendship grounded on the concept of 'kapwa' (fellow). Some of the norms linked to kappa are pakikipagkapwa-tao (human fellowship), pakikisama (adjusting), pakikitungo (civility), pakikiramay (sympathy), pakikiisa (unity) and pakikibaka (cooperative resistance). Other cultural aspects of the Filipino are also given emphasis such as the concepts of barcode, hospitality, bayanihan (togetherness) and utang na look (debt of gratitude). This paper tries to argue which of these norms follows Aristotle's standard for a lasting friendship.
Keywords: Ethics; Friendship; Aristotle philosophy